Assessing Information and Communicative Competence of Future Special Education Teachers in the Use of Resources of the Informational Educational Environment - Artemova E.E; Danilova A.M; Podvalnaya E.V; Tishina L.A (Moscow State University of Psychology and Education, 2021)
This article aims to analyse the problem of developing the readiness to use re- sources and services of the informational educational environment in work and study in students of pedagogical universities (future special educational needs (SEN) teachers). The urgency of creating technologies for practice-oriented train- ing of future SEN teachers (speech pathologists, teachers of individuals with hearing and visual impairments, teachers of children with mental retardation) is caused by the increasing requirements to the training of such specialists. The article presents results of an experimental study on the levels of information and communicative competence in first- and second-year students (N=114) of bachelor programmes in special education of children with disabilities. We used the following methods in our study: online questionnaires, pedagogical observation, practical tasks and tests within certain courses, and analysis of students' works that were conducted using ICT (information and communication technologies). The criteria that we established for assessing the general user, pedagogical and subject components of ICT competence allowed us to determine its levels in bachelor students. The analysis of the data obtained in our study helped to identify the areas of concern and the necessary elements in the training of future special education teachers.